Upaya Peningkatan Kecerdasan Spiritual Anak Panti Asuhan Keluarga Bunga Bakung Terhadap Aksi Sosial Masyarakat Sebagai Implementasi Kasih - Elsi Susanti Simamora; Maria Lidya Wenas (Sekola Tinggi Teologi Sangkakala Jakarta, 2022)
Spiritual intelligence is the ability possessed by a person to knowing and understanding the truth of God's Word. The aim of this research is to find out what are the efforts of the leaders of the Bunga Lilies Orphanage in increasing the spirituality of foster children towards community social action as the implementation of love. In collecting data, this study used a qualitative descriptive method by conducting interviews, observations and literature studies. So the results of this study indicate that in an effort to increase the spiritual intelligence of children in family orphanages, there are several things that can be done, namely by conducting prayer activities, reading Bible movements, procuring evangelism to villages, and holding social actions to the community. The efforts that have been made have become the embodiment of the implementation of love as evidence of the increasing spiritual intelligence of the orphanage children.